Clinical analysis of the state of the temporomandibular joints in adult patients with juvenile idiopathic arthritis - Etnis, Л. О.; Zhegulovich, З. Є.; Symonenko, Р. В.; Sayapina, Л. М. (Actual Dentistry, 2022)
Relevance. Juvenile idiopathic arthritis (J IA) is a systemic connective tissue disease with predominant localization of the process in the musculoskeletal system. According to the results of the study [3], temporomandibular joint disease (TMJ) was detected in 4.7±3.2 % of patients with JIA. Therefore, in our opinion, the problem of musculo-articular disorders and diseases of the temporomandibular joints (TMJ) against the background of this pathology is quite relevant. The aim of this study was to conduct a clinical analysis of the state of the temporomandibular joints in adults with juvenile idiopathic arthritis against the background of dentoalveolar anomalies and deformities. Materials and research methods. A retrospective analysis of extracts from the medical history of 26 adults (17 women (65.4 %)) and 9 men (34.6 %) who had juvenile idiopathic arthritis and had long-term joint and extra-articular consequences and have long-term articular and extra-articular complications in adulthood was carried out. A clinical analysis of the state of the temporomandibular joints, occlusion and manifestations of pain in these individuals and in 25 individuals of the control group was carried out. Results of the study and their discussion. Bilateral dysfunctional, inflammatory and degenerative joint lesions were identified in 14 (53.8%) individuals of the observation group, bilateral asymmetrical lesions (a combination of dysfunctional, inflammatory and degenerative processes) in 9 people (34.6%). In 3 (11.6%) individuals, signs of dysfunction and diseases of the TMJ were not identified. Pain in the observation group was defined as extremely mild to moderate, with only 5 people (19.2%) reporting very severe pain. The presence of dentoalveolar anomalies and deformities was determined in 53.8% of patients with JIA and 44% of persons in the control group. Conclusions. The obtained results confirm the polyetiological nature of dysfunctional conditions and diseases of the temporomandibular joint and indicate directions for the development oftherapeutic and preventive measures for patients with JIA.